Assessment of the Polish Diaspora's Access to Education in the Toronto Metropolitan Area and Their Evaluation of the Level of Education in the Context of Quality of Life - Kamila Ziółkowska-Weiss (Ignatianum University Press, 2022)
The main objective of the article is to depict access to education, both in terms of objective factors (quality of life) and subjective factors (standard of living), in the assessment of the Polish community living in the greater Toronto metropolitan area (GTA). The results of the research are presented on the basis of a questionnaire conducted among 583 Polish people living in the GTA. The results confirm that the Canadian Polish community evaluates highly the schools and other educational institutions operating within the study area. Another goal of the research was to investigate the possible influence of gender, income, or household size on the evaluation of access to education, which translates into a higher assessment of quality of life. In the study, the women and the respondents with higher income rated access to education more highly, while people in households with two to four people evaluated it the highest.